Upor proti dolgčasu - Hiti Ožinger, Pino (Retrospektive, 2025)
The emergence of punk in Slovenia at the end of the 1970s represents the transference of a rebellious subculture that was emerging in the capitalist West into a socialist context, which then prescribed its own currents of development. Slovenia was also the first of the Yugoslav republics in which punk emerged, and therefore Ljubljana in particular can be seen as one of the main centres of Yugoslav alternative culture. The papers presents the origins of punk in Slovenia, its development and a reflection on the type of rebellion it represented. Punk in Slovenia was both political and anti-political, as it attempted to open up the boundaries of expression that had no foundation in the dominant political discourse of the time. The paper also presents the path punk theory took into the liberal framework of the newly emerging civil society in Slovenia.
Keywords: civil society; civilna družba; politics; politika; punk; rebellion; Slovenia; Slovenija; socialism; socializem; subculture; subkultura; upor